USING CONTEMPORARY TECHNOLOGIES TO TEACH TECHNICAL DISCIPLINE STUDENTS VOCABULARY IN ENGLISH - Turaboeva Komila Eshmakhmatovna (Bright Mind Publishing, 2025)
The goal of contemporary English vocabulary teaching methods for technical university students is to enhance and maximize their acquisition of specialized and technical terminology. Students at technical universities need to be able to employ professional terminology in a variety of languages, particularly English, given the globalization and the speed at which science and technology are developing. This task can be completed more successfully with the aid of modern technologies. These technologies' primary benefits include the usage of interactive webinars and online courses, corpus technologies and text analysis, games in the classroom, digital educational platforms, multimedia resources, and artificial intelligence technology. By incorporating these tools into the classroom, students become more motivated, learning is tailored to meet their needs, and the process of learning technical jargon is greatly accelerated.
Keywords: Technologies, professional terminology, motivation, technical subjects, communication, comprehension, interpretation, competence-based approach, Internet technologies.